Pengaruh Penggunaan Kamus Mnemonik Sebagai Sumber Belajar Terhadap Hasil Belajar Sejarah Siswa di SMA - Ilham Gazali; Ofianto Ofianto (Jurusan Sejarah FIS UNP, 2020)
This research is motivated by the lack of students' understanding of the subject matter of history, especially in remembering facts and concepts in learning history, so that it influences student learning outcomes. One of the causes of the low learning outcomes of history is due to the lack of varied learning resources. To overcome these problems, one alternative learning resource that can be used is the mnemonic dictionary. This study aims to look at the effect of using mnemonic dictionaries as learning resources on student history learning outcomes in high school. This type of research is a quasi-experimental type. The sample used is class X IPA2 as an experimental class and class X IPA1 as a control class at SMAN 12 Padang. Whereas in Pariaman 3 Public High School the sample used class X IPS2 as an experimental class and class X IPS4 as a control class. Test score data were analyzed using quantitative analysis in the form of a t test. After the t test is a one-sided t-test of the experimental class's posttest data the experimental class's posttest data with a significance level of 0.05, the results obtained are at 12th Padang High School which is 2.840> 1.670 and in SMAN 3 Pariaman is 2.064> 1.673. Because thit> ttab, H0 is rejected and H1 is accepted. Then it can be concluded that there is a significant influence on the use of mnemonic dictionaries as a learning resource on the learning outcomes of students' history in high school.